Deliberations About Genomic Research and Biobanks With Citizens of the Chickasaw Nation - Reedy, Justin; Blanchard, Jessica W.; Lund, Justin; Spicer, Paul G.; Byars, Christie; Peercy, Michael; Saunkeah, Bobby; Blacksher, Erika (Frontiers in Genetics, 2020)
Amid the rapid growth of precision medicine and biobanking initiatives, there have been few efforts at cataloguing the implications of these initiatives for Indigenous communities. A consortium involving a university and three American Indian/Alaska Native (AIAN) community partners is working to promote deliberation and dialogue in AIAN communities about the potential benefits and risks of genomic research for those communities. The first of the consortium’s three planned deliberations was held in September 2018 with citizens of the Chickasaw Nation, a federally recognized tribe in south-central Oklahoma with a full-service medical center and growing research capacity and oversight. Consortium members and the Chickasaw Nation Department of Health Administration designed a deliberative forum for Chickasaw citizens to consider the potential benefits and risks of participating in genomic research and biobanks. In this manuscript, we describe the deliberative method used in this event and report on the ideas discussed during the tribal citizens’ deliberations. Chickasaw citizens identified many risks and benefits associated with genomic research and biobanks, including the potential for medical advancements that might benefit the Chickasaw community as well as the possibility of discrimination against the Chickasaw people. Although participants thought the potential benefits outweighed the potential risks, that moral calculation was contingent on whether control of the research and biobanks rested with Chickasaw leadership, researchers, and citizens.